2021
DOI: 10.1038/s41467-021-23865-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of specific non-pharmaceutical intervention policies on SARS-CoV-2 transmission in the counties of the United States

Abstract: Non-pharmaceutical interventions (NPIs) remain the only widely available tool for controlling the ongoing SARS-CoV-2 pandemic. We estimated weekly values of the effective basic reproductive number (Reff) using a mechanistic metapopulation model and associated these with county-level characteristics and NPIs in the United States (US). Interventions that included school and leisure activities closure and nursing home visiting bans were all associated with a median Reff below 1 when combined with either stay at h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…In the simulations presented in the main text we used r = 1.3 imagining a scenario where the relaxation of COVID safe behaviors increases the transmission rate of 30%. This choice is informed by the estimated effects of NPIs such as face masks and social distancing on COVID-19 spreading, as reported in the literature [ 4 , 20 , 81 , 82 ]. Nonetheless, in the S1 Text we perform a sensitivity analysis considering also r = 1.1, 1.5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the simulations presented in the main text we used r = 1.3 imagining a scenario where the relaxation of COVID safe behaviors increases the transmission rate of 30%. This choice is informed by the estimated effects of NPIs such as face masks and social distancing on COVID-19 spreading, as reported in the literature [ 4 , 20 , 81 , 82 ]. Nonetheless, in the S1 Text we perform a sensitivity analysis considering also r = 1.1, 1.5.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, they are linked to socio-economic, socio-demographic features, and education attainment [ 18 ]. Arguably, vaccines alone will not be able to contain the spreading of the virus, at least in the short term [ 19 , 20 ]. Social distancing, face masks, hygiene measures, and other NPIs will be still key during the delivery of such vaccination programs, especially considering the emergence of variants of concern as well as the challenges in vaccines procurement and administration in the developing world [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…We use vaccine eligibility data from the COVID-19 U.S. State Policy Database maintained by Boston University (Raifman et al 2020). The data contain detailed information on state-level policies enacted during the COVID-19 pandemic and have been used to evaluate the effect of state-level policies on COVID-19 transmission and physical distancing (Feyman et al 2020;Yang et al 2021;Jay et al 2020). We use the age-based vaccine eligibility dates to determine whether an individual is eligible for a vaccine within a state.…”
Section: Vaccine Eligibility Datamentioning
confidence: 99%
“… 2 , 3 , 4 In addition, effective nonpharmaceutical interventions, such as medical masks or physical distancing, cannot be applied for preschool children. Despite differences between influenza viruses and SARS-CoV-2, 5 modeling studies 6 , 7 , 8 have suggested that closure of schools and DCCs might be beneficial in limiting the dissemination of SARS-CoV-2. However, other models 9 , 10 support reopening of childcare facilities, suggesting that they have only a minor impact on viral spreading in the population or disproportionate negative effects.…”
Section: Introductionmentioning
confidence: 99%